Perbedaan Aktivitas Belajar dan Hasil Belajar antara Model Pembelajaran Kooperatif Tipe Jigsaw dengan Model Direct Instruction pada Kompetensi Pembuatan Pola Kebaya Siswa Fase F Tata Busana SMKN 8 Surabaya - Maharani, Erizma; Lutfiyah Hidayati; Marniati Marniati (CV. KAMPUS AKADEMIK PUBLISHING, 2025)
This study aims to: 1). Analyze the differences in students’ learning activities between the implementation of the cooperative learning model Jigsaw and the Direct Instruction model in the kebaya pattern-making competency of Phase F students at SMKN 8 Surabaya. 2). Analyze the differences in students’ learning outcomes between the cooperative learning model Jigsaw and the Direct Instruction model in the kebaya pattern-making competency of Phase F students at SMKN 8 Surabaya. This research is a quantitative study employing a non-parametric difference test using the Mann-Whitney U test. The study was conducted at SMKN 8 Surabaya with 31 Phase F Fashion Class 1 students in April using the cooperative learning model Jigsaw, and 31 Phase F Fashion Class 2 students in February using the Direct Instruction model. Data collection techniques consisted of observation sheets to assess learning activities during the learning process in both classes the experimental class using the Jigsaw cooperative learning model and the control class using Direct Instruction. In addition, a post-test was administered to measure students’ learning outcomes after the implementation of each learning model. The results of the study show that: 1). There is no significant difference in students’ learning activities between the use of the cooperative learning model Jigsaw and the Direct Instruction model. 2). There is a significant difference in students’ learning outcomes between the use of the cooperative learning model Jigsaw and the Direct Instruction model.